PARAMETERS OF SOMATIC CENTRAL HEMODYNAMICS AT ATHLETES AND FOOTBALL PLAYERS - Sarafinyuk, L.A.; Lezhneva, E.V. (World of Medicine and Biology, 2012)
The article features established correlations between indices of central hemodynamics and anthropometric dimensions, somatotype components and body mass indices and postural carpal dynamometry at athletes and footballers adolescence high level of sportsmanship.
Keywords: correlation; central hemodynamics; anthropometry; somatotype; body mass; athletes; football players